2017
DOI: 10.1111/apa.13784
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular hyperfiltration is strongly correlated with age in Congolese children with sickle cell anaemia

Abstract: Glomerular hyperfiltration was a common finding in this study and was significantly associated with age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
(38 reference statements)
4
9
2
Order By: Relevance
“…Thirty six children (35.6%) in the present study had GH, this prevalence was consistent with 33.1% [9] and 40% [14] in Congolese children, where eGFR was estimated using the same method, but lower than 76% and 72.9% reported by two different American studies [7,10]. Variation in the prevalence rate of glomerular hyper iltration between studies is not clearly understood, but it could be in luenced by inconsistency in population characteristics, the methods used to estimate or measure GFR, and the cut-offs used to de ine hyper iltration.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Thirty six children (35.6%) in the present study had GH, this prevalence was consistent with 33.1% [9] and 40% [14] in Congolese children, where eGFR was estimated using the same method, but lower than 76% and 72.9% reported by two different American studies [7,10]. Variation in the prevalence rate of glomerular hyper iltration between studies is not clearly understood, but it could be in luenced by inconsistency in population characteristics, the methods used to estimate or measure GFR, and the cut-offs used to de ine hyper iltration.…”
Section: Discussionsupporting
confidence: 88%
“…Current evidence provided by a longitudinal cohort study of 91 children with SCD, showed glomerular hyper iltration to precede the development of persistent albuminuria, and children with early hyper iltration are predispose to develop early microalbuminuria [13]. Microalbuminuria is another initial https://doi.org/10.29328/journal.jcn.1001065 marker of SCN tends to increase with age in parallel to decline of GFR [14], and it has been reported at a rate ranged between 11.3% -51.3% in children, and up to 68% in adults [15].…”
Section: Introductionmentioning
confidence: 99%
“…Second, our natural history data show a decline from hyperfiltration beginning around 10‐13 years of age after which time we identified no difference in eGFR between those participants with and without albuminuria. This finding may explain why several cross‐sectional studies, including our prior studies, evaluating eGFR at the time adolescent patients develop episodes of albuminuria have not identified an association of hyperfiltration and albuminuria . Finally, additional research, potentially using biomarkers of glomerular or tubular injury are needed to better understand or predict patients at risk for progression to hyperfiltration.…”
Section: Discussionmentioning
confidence: 95%
“…This study's finding that none of the factors examined was associated with glomerular hyperfiltration is at variance with previous studies. In the paediatric age group, the only available research on the determinants of glomerular hyperfiltration [10], reported that older age and reduced body mass index were factors associated with glomerular hyperfiltration. However, this study cannot be compared to the previous study because their definition of glomerular hyperfiltration differs.…”
Section: Discussionmentioning
confidence: 99%
“…Its aetiology in SCD is not clearly understood but, its development and progression are believed to be driven by increased glomerular perfusion and increased effective glomerular filtration surface area, but not by increased glomerular capillary hydrostatic pressure [7]. The reported prevalence of glomerular hyperfiltration in SCD, mainly in children with SCA, ranges from 40% to 98% [8] [9] [10]. These prevalence rates differ from study to study because there is no uniform definition of glomerular hyperfiltration.…”
Section: Introductionmentioning
confidence: 99%